2018
DOI: 10.1021/jacs.8b04040
|View full text |Cite
|
Sign up to set email alerts
|

Family of BODIPY Photocages Cleaved by Single Photons of Visible/Near-Infrared Light

Abstract: Photocages are light-sensitive chemical protecting groups that provide external control over when, where, and how much of a biological substrate is activated in cells using targeted light irradiation. Regrettably, most popular photocages (e.g., o-nitrobenzyl groups) absorb cell-damaging ultraviolet wavelengths. A challenge with achieving longer wavelength bond-breaking photochemistry is that long-wavelength-absorbing chromophores have shorter excited-state lifetimes and diminished excited-state energies. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
282
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(308 citation statements)
references
References 49 publications
5
282
2
6
Order By: Relevance
“…Moreover, Smith and Winter recently developed π‐extended BODIPY derivatives (e.g. compound 48 in Scheme ) featuring light absorptions above 700 nm, the longest wavelengths ever reported for photocage activation with single‐photon irradiation . However, since these photocages often include hydrolytically labile ester bonds, it is not clear whether the plasma stability may limit future translational programs.…”
Section: When and Where: Linker Cleavage Promoted By External Stimulimentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Smith and Winter recently developed π‐extended BODIPY derivatives (e.g. compound 48 in Scheme ) featuring light absorptions above 700 nm, the longest wavelengths ever reported for photocage activation with single‐photon irradiation . However, since these photocages often include hydrolytically labile ester bonds, it is not clear whether the plasma stability may limit future translational programs.…”
Section: When and Where: Linker Cleavage Promoted By External Stimulimentioning
confidence: 99%
“… A) Examples of π‐extended photosensitive linkers, cleavable by either two‐photon (TP, as compound 47 ) or single‐photon (SP, compound 48 ) excitation with NIR wavelengths. B) ADC 49 developed by Schnermann and co‐workers, based on a NIR light‐sensitive cyanine linker, a duocarmycin (Duo) payload and a diamine‐based self‐immolative spacer (depicted in green) …”
Section: When and Where: Linker Cleavage Promoted By External Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…Several chemical approaches for increasing the hydrolytic stability of the linker are available, including the use of 2′‐MeO‐ or phosphorothioate‐modified DNA, or the use of protein nucleic acids (PNAs) or locked nucleic acids (LNAs) . Similarly, a variety of red‐light‐activatable photocleavable ligands have recently been reported that could be used to avoid the potential phototoxicity of 365 nm light and to allow deeper tissue penetration …”
Section: Figurementioning
confidence: 99%
“…Photoreleased molecules are of considerable interest not only in the field of photochemistry but also in site‐specific delivery applications . Current literature on sensitizer and drug photorelease has mainly focused on the use of direct UV, visible and near‐IR light to activate the release mechanisms.…”
Section: Introductionmentioning
confidence: 99%